2020
DOI: 10.1007/978-3-030-60073-0_25
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Customers’ Emotional Experience? A Short Review of Current Methods and a Call for Neurophysiological Approaches

Abstract: In the digital age, retailers compete through various sales channels, both online and offline, with the effect that the customers' experiences have increasingly gained attention in the omnichannel era. Specifically, customer emotions have become an important topic, because they affect attitudes towards products and services as well as purchase decisions. While the phenomenon of customer experience is widely researched, surprisingly, to the best of our knowledge, no peer-reviewed journal publication exists that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Overall, our findings can be explained by the lack of haptic product information available to online customers ( Citrin et al, 2003 ), which makes it more difficult for customers with high NFT to evaluate a product’s quality ( Kühn et al, 2020 ). Because we know that emotions play a crucial role in the customer experience ( Gentile et al, 2007 ; Puccinelli et al, 2009 ; Hermes and Riedl, 2020a , b , 2021a ), it is surprising that Autotelic NFT did not evince a significant association with either online or in-store willingness to purchase. However, it must be observed that the study data were collected in the midst of the COVID-19 pandemic, during which a notable number of customers have perceived in-store shopping as vector of infection and took corresponding precautions that might disrupt or mitigate Autotelic NFT (e.g., disinfecting their hands; Szymkowiak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our findings can be explained by the lack of haptic product information available to online customers ( Citrin et al, 2003 ), which makes it more difficult for customers with high NFT to evaluate a product’s quality ( Kühn et al, 2020 ). Because we know that emotions play a crucial role in the customer experience ( Gentile et al, 2007 ; Puccinelli et al, 2009 ; Hermes and Riedl, 2020a , b , 2021a ), it is surprising that Autotelic NFT did not evince a significant association with either online or in-store willingness to purchase. However, it must be observed that the study data were collected in the midst of the COVID-19 pandemic, during which a notable number of customers have perceived in-store shopping as vector of infection and took corresponding precautions that might disrupt or mitigate Autotelic NFT (e.g., disinfecting their hands; Szymkowiak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another integral part of the customer journey is physical engagement with (that is, the touching of) a product ( Roggeveen et al, 2020 ), which helps consumers to form impressions of that product ( Ranaweera et al, 2021 ), but individuals differ in their Need for Touch (NFT). While affect and cognition play important roles in the customer experience ( Gentile et al, 2007 ; Puccinelli et al, 2009 ; Hermes and Riedl, 2020a , b ), NFT can also be motivated by enjoyment and pleasure (affective side, so-called Autotelic NFT) or to receive product information, such as a product’s weight or quality (based on analytic thoughts, goal-driven, so-called Instrumental NFT, Peck and Childers, 2003a ). Online consumption lacks the element of touch ( Peck and Childers, 2003a ), and accordingly, online customers displayed lower levels of NFT ( San-Martín et al (2017) ; however, Duarte and Costa e Silva (2020) did not confirm this finding).…”
Section: Introductionmentioning
confidence: 99%
“…Additional Examination of Direct and Mediated Effects in the Personality-Channel Relationship. From a large amount of research on customer experience, we know that personal factors, especially emotions [64][65][66][67][68][69], play an overarching role in a customer's shopping experience. Researchers have argued that emotions can be separated into incidental (task-unrelated, highly influenced by personality) and integral (task-related) emotions [70].…”
Section: Research Agenda and Managerial Implications 41 Research Agendamentioning
confidence: 99%
“…We adopted Phillips’ (1997) to measure creative self-efficacy, which correspond to four questions: CE1-CE4 (see Table 3 ). We adopted Hermes and Riedl (2020) to measure positive emotional experience with four questions, corresponding to PM1-PM4. Furthermore, this study used Woodman et al (1993) customer creativity scale with three questions (CC1-CC3) in Table 3 We included four control variables because the prior empirical work has suggested that “education level,” “participation frequency,” “income level,” and “age structure” have potential influence on creativity.…”
Section: Methodsmentioning
confidence: 99%